The Collision of Ships at Sea: Problems of Responsibility and Jurisdiction - N. A. Butakova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The purpose of this article is to review the main problems of liability and jurisdiction in the collision of ships at sea. The collision of ships is one of the most common accidents at sea, entailing further legal consequences. A collision is the physical contact of vessels with each other as a result of the approach or incorrect maneuver of one of the vessels, as a result of which the other vessel, in order to avoid a collision, is forced to run aground. This article deals with the limitation of liability in the collision of ships and the distribution of liability between shipowners. The article contains an analysis of possible options for determining the jurisdiction in a collision of courts, as well as the specifics and features of the definition of such jurisdiction.